PENGARUH KEDALAMAN GROUTING SEMEN SEBAGAI LANGKAH MITIGASI PENURUNAN TANAH BERMASALAH PADA BANGUNAN SATU LANTAI DI KABUPATEN WONOSOBO - Rahma, Rafinda; Galuh Chrismaningwang; Niken Silmi Surjandari (INDONESIAN JOURNAL OF ENVIRONMENT AND DISASTER, 2025)
Organic soils are characterized by low bearing capacity, which poses significant challenges in construction projects. This issue is exemplified in a one-story shop building located in the Dieng area, Wonosobo Regency, which has suffered severe structural damage after 7 years. One of the remediation methods employed to address this problem is cement grouting. This study aims to assess the impact of grouting depth on the settlement behavior of organic soil. The depths evaluated were 15 cm, 30 cm, and 50 cm. Settlement analysis was conducted using Plaxis 2D software with a Soft Soil Creep model, deemed suitable for calculating both primary and secondary consolidation settlements, representative of organic soils. The initial soil condition without grouting was analyzed as a control for the three variations in grouting depth. The analysis results indicated that the settlement in the initial condition was 42.85 cm. The settlements at depths of 15 cm, 30 cm, and 50 cm were 39.65 cm, 36.21 cm, and 30.86 cm, respectively. The corresponding deviations in settlement for depths of 15 cm, 30 cm, and 50 cm were 7.47%, 15.49%, and 27.99%, respectively. The analysis results demonstrate that greater grouting depths result in reduced settlement magnitudes.